Hierarchical virtual inertia control of DC distribution system for plug-and-play electric vehicle integration. (June 2021) - Peng, Ke; Wei, Zhiyu; Chen, Jiajia; Li, Hairong
Highlights: Hierarchical virtual inertia control to enhance the anti-interference ability. The local virtual inertia control to suppress system fluctuation caused by EV access. The system virtual inertia control to suppress fluctuation caused by load change. The numerical examples verified the proposed control strategy. Abstract: DC distribution system will play a significant role in future urban distribution system, while the integration of electric vehicle has a tremendous influence on the stability of DC distribution system. This paper presents an assessment and mitigation strategy of such negative impact on DC distribution system. Mathematical modelling and analysis of the load/source admittances are provided to evaluate the overall system stability based on the Nyquist admittance ratio criterion. The theoretical analysis shows that the integration of electric vehicle introduces incremental negative admittances which significantly degrades the system stability. Therefore, a hierarchical virtual inertia control strategy, consisted of a local-level control and a system-level control, is proposed to improve the system damping and suppress the negative influence. The local-level virtual inertia control can suppress the instability caused by electric vehicle integration, while the disturbance caused by the fluctuations of other DC loads or sources can be suppressed by the system-level virtual inertia control. Numerical examples verify the effectiveness of the method, which can improve the stability of DC distribution system and satisfy the requirement of electric vehicle plug-and-play.